Outcome in Hodgkin's lymphoma can be predicted from the presence of accompanying cytotoxic and regulatory T cells. - Alvaro, T; Lejeune, M; Salvadó, M; Bosch, R; García, J; Jaén, J; Banham, A; Roncador, G; Montalbán, C; Piris, M (2005)
PURPOSE: Recent studies of Hodgkin's lymphoma (HL) have suggested that the presence of regulatory T cells in the reactive background may explain the inhibition of the antitumoral host immune response observed in these patients. This study aimed to assess the relevance of regulatory T cells and CTLs present in the background of HL samples in the prognosis of a series of classic HL (cHL) patients. EXPERIMENTAL DESIGN: Expression of granzyme B and TIA-1 (markers for CTL) and FOXP3 (a marker for regulatory T cells) were evaluated independently by immunohistochemistry in tissue microarrays of 257 cHL patients and correlated with patient outcome. RESULTS: The combined influence of the presence of FOXP3(+) and TIA-1(+) cells distinguished three risk groups of patients with 5-year overall survival of 100%, 88%, and 73%. The presence of a small number of FOXP3(+) cells and a high proportion of TIA-1(+) cells in the infiltrate represent an independent prognostic factor that negatively influenced event-free survival and disease-free survival in cHL. Compared with the features at diagnosis, relapsed samples tended to have more TIA-1(+) cells and a lower proportion of FOXP3(+) cells in the reactive background. CONCLUSIONS: These data suggest that low infiltration of FOXP3(+) cells in conjunction with high infiltration of TIA-1(+) cells in cHL may represent biological markers predicting an unfavorable outcome. Moreover, the variation of these markers over the course of the disease implies a possible role for them in the progression of HL cases.